Slums on Screen - Krstić, Igor (Edinburgh University Press, 2022)
From Jacob Riis’ How The Other Half Lives (1890) to Danny Boyle’s Slumdog Millionaire (2008), Igor Krstić outlines a transnational history of films that either document or fictionalise the favelas, shantytowns, barrios poulares or chawls of our ‘planet of slums’.